Testing for Serial Correlation in Simultaneous Equation Models - Harvey, A. C.; Phillips, G. D. A. (Econometrica, 1980)
[This paper presents the theoretical development of bounds tests and exact tests for serial correlation in the context of a simultaneous equation model which are analogous to those developed for single equation models. The powers of the exact tests are estimated and compared using Monte Carlo simulation of a three equation model.]